The Effect of Product Quality and Service Quality on Consumer Repurchase Intention of Alami Restaurant & Catering Service with Customer Satisfaction as an Intervening Variable - Nadia Khansa Salsabila (Universitas Ciputra Surabaya, 2023)
This study examines the direct and indirect effects of product quality and service quality on the repurchase interest of Alami Restaurant & Catering Service consumers with customer satisfaction as an intervening variable. The variables studied were product quality (X1), service quality (X2), customer satisfaction (Y1), and repurchase interest (Y2). The respondents of this study were all customers of Alami Restaurant & Catering Service and this quantitative research distributed questionnaires to 270 customers of Alami Restaurant & Catering Service as respondents determined by purposive sampling techniques, namely customers who came directly to the restaurant and had made a minimum purchase once at the restaurant. The results found that 1) product quality has a positive and significant effect on customer satisfaction value of 0.000 p ≤ 0.05; 2) service quality of 0.000 p ≤ 0.05 has a positive and significant effect on customer satisfaction; 3) product quality has a positive effect on customer repurchase interest value 0.003 p ≤ 0.05 and 4) service quality has a positive and significant effect on repurchase interest value 0.000 p ≤ 0.05; and 5) product quality and service quality positively affect repurchase interest with partial mediation of customer satisfaction 0.000 p ≤ 0.05.